LEKTI domains D6, D7 and D8+9 serve as substrates for transglutaminase 1: implications for targeted therapy of Netherton syndrome. (1st November 2019) - Wiegmann, H.; Valentin, F.; Tarinski, T.; Liebau, E.; Loser, K.; Traupe, H.; Oji, V.
Summary: Background: Transglutaminase (TG)1 plays a key role in the formation of the cornified envelope and thus in the maintenance of the epidermal barrier. Patients with Netherton syndrome (LEKTI deficiency) have increased activity of both TG1 and serin proteases. Objectives: To determine whether there is a functional biochemical link between TG1 and LEKTI and whether LEKTI domains could possibly serve as substrates for TG1. Methods: We analysed the protein sequence of LEKTI for possible TG1 recognition sites using bioinformatics. Synthetic peptides and recombinant LEKTI domains D6, D7 and D8+9 were examined in vitro and in situ for possible substrate specificity. The recombinant LEKTI domains were studied for inhibitory activity in a kallikrein (KLK)5 activity test. Results: We identified possible TG1 consensus sequences in LEKTI domains D6, D7 and D8+9, pointing to a novel biological link between these two proteins. Indeed, synthesized short peptides from these consensus sequences were incorporated into the TG1 activity zone of the epidermis. In vitro the entire recombinant domains of LEKTI showed substrate specificity for TG1, which was again confirmed in situ . The inhibitory activity of the recombinant LEKTI domains was confirmed by a KLK5 inhibition test. The strongest inhibition was observed for domains D8+9. Conclusions: There are specific domains of LEKTI that are recognized and processed by TG1. LEKTI domains D6, D7 and D8+9 contribute to the formation and protection of the cornified envelope. These results impact the development of protein replacement therapy approaches for Netherton syndrome. What's already known about this topic? LEKTI and transglutaminase (TG)1 are key proteins involved in the terminal differentiation of the epidermis. Lack of LEKTI causes Netherton syndrome; TG1 deficiency causes lamellar ichthyosis. The serine protease inhibitor LEKTI is processed into different functional units. Among different target proteases, kallikrein (KLK)5 appears to be a key player in disease pathology. It has been demonstrated that LEKTI domain 6 inhibits KLK5 and KLK7; LEKTI domains 8–11 also inhibit KLK14. What does this study add? The single LEKTI domains 6, 7 and the functional unit of domains 8 and 9 contain recognition motifs for TG1. We show that these domains and unit are crosslinked into the epidermis by TG1. Functional analyses of the recombinant LEKTI domains revealed that LEKTI D8+9 has the strongest inhibitory effect on KLK5. What is the translational message? The novel functional link between LEKTI and TG1 should be taken into account when considering the development of a targeted topical protein therapy for Netherton syndrome. The unit of domains D8+9 may be sufficient for this purpose.